Full-field measurement and fracture characterisations of rocks under dynamic loads using high-speed three-dimensional digital image correlation. (March 2018) - Xing, H.Z.; Zhang, Q.B.; Ruan, D.; Dehkhoda, S.; Lu, G.X.; Zhao, J.
Highlights: Full-field strain and strain-rate fields of rock was obtained by high-speed 3D-DIC. The 256 × 256 pixels and 200, 000 fps are suggested in dynamic measurement of rock. Wave propagation, dispersion and radial inertial effect on the specimen were found. The comparison was conducted between 2D- and 3D-DIC in strain measurement. The failure of sandstone is a shear mode in the test of split Hopkinson pressure bar. Abstract: Full-field strain and strain-rate fields of rock materials under dynamic compression were studied by the high-speed three-dimensional digital image correlation (3D-DIC) method. A series of dynamic tests was conducted on Hawkesbury sandstones using a split Hopkinson pressure bar (SHPB) at three different strain rates. The real-time images of the loaded specimen were captured by two high-speed cameras at a frame rate of 200, 000 frames per second (fps) with a resolution of 256 × 256 pixels. Wave propagation, dispersion and radial inertial effect on the specimen were found by DIC results. The strain rate vibration pattern on the specimen, which was visualised by DIC, found to be dependent on the input waveform. A recovery of strain in the post-peak stage was detected on the specimen by DIC, which is unrevealed in the traditional one-dimensional theory method (i.e., strain gauge signals). The results showed that strain localisation initiated from the interface of the bar and specimen with the order of tensile, shear and vertical. The initiation of crack from strain localisation is found rate-independent. Comparison between 2D- and 3D-DIC in strain measurement of the same experiment showed that the error in the strain obtained by 2D-DIC could be up to 32%.